2010
DOI: 10.1017/s1049096510990689
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Learning Outcomes in United States Government Courses

Abstract: This study employs the Solomon Four-Group Design to measure student knowledge of the United States government and student knowledge of current events at the beginning of a U.S. government course and at the end. In both areas, knowledge improves significantly. Regarding knowledge of the U.S. government, both males and females improve at similar rates, those with higher and lower GPAs improve at similar rates, and political science majors improve at similar rates to non-majors. Regarding current events, males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In performing rigorous evaluation of student learning in the class, we bring the broader principles of the assessment movement to bear on a single class. On assessment in political science, see Champney and Edleman (2010) and Deardorff, Hamann, and Ishiyama (2009). 14. These survey questions are taken from Bos and Schneider's (2009) study of student learning in methods courses.…”
Section: Discussionmentioning
confidence: 99%
“…In performing rigorous evaluation of student learning in the class, we bring the broader principles of the assessment movement to bear on a single class. On assessment in political science, see Champney and Edleman (2010) and Deardorff, Hamann, and Ishiyama (2009). 14. These survey questions are taken from Bos and Schneider's (2009) study of student learning in methods courses.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment was inspired by the possibility that political science might help us to “understand the manner in which complex current events are relevant to our own lives due to increasing levels of social, economic, and political interdependence” (Hauss 1995). Champney and Edleman (2010) provided evidence that students’ knowledge about current events increases with political science courses. As a result, scholars have offered advice on how to incorporate current events in courses.…”
Section: Defining Treatmentsmentioning
confidence: 99%
“… 14 In their study of relationship between taking American government classes and knowledge gain, Champney and Edelman (2010) found that those students with low and high GPAs had similar patterns in improvement in background knowledge, but those students with higher GPAs gained relatively more in knowledge of current events. They note that other studies indicate that higher GPAs are associated with greater gains in students' background knowledge.…”
Section: Notesmentioning
confidence: 99%